Manganese Oxide Nanoparticles As MRI Contrast Agents In Tumor Multimodal Imaging And Therapy - Cai X (Dove Medical Press, 2019)
Xiaoxia Cai, Qingxia Zhu, Yun Zeng, Qi Zeng, Xueli Chen, Yonghua Zhan Engineering Research Center of Molecular and Neuro Imaging of the Ministry of Education, School of Life Science and Technology, Xidian University, Xi’an, Shaanxi, People’s Republic of ChinaCorrespondence: Yonghua ZhanEngineering Research Center of Molecular and Neuro Imaging of the Ministry of Education, School of Life Science and Technology, Xidian University, Xi’an, Shaanxi 710071, People’s Republic of ChinaTel +86 29 81891070Fax +86 29 81891060Email yhzhan@xidian.edu.cnAbstract: Contrast agents (CAs) play a crucial role in high-quality magnetic resonance imaging (MRI) applications. At present, as a result of the Gd-based CAs which are associated with renal fibrosis as well as the inherent dark imaging characteristics of superparamagnetic iron oxide nanoparticles, Mn-based CAs which have a good biocompatibility and bright images are considered ideal for MRI. In addition, manganese oxide nanoparticles (MONs, such as MnO, MnO2, Mn3O4, and MnOx) have attracted attention as T1-weighted magnetic resonance CAs due to the short circulation time of Mn(II) ion chelate and the size-controlled circulation time of colloidal nanoparticles. In this review, recent advances in the use of MONs as MRI contrast agents for tumor detection and diagnosis are reported, as are the advances in in vivo toxicity, distribution and tumor microenvironment-responsive enhanced tumor chemotherapy and radiotherapy as well as photothermal and photodynamic therapies.Keywords: manganese oxide nanoparticles, MRI, multimodal imaging, contrast agent, tumor therapy